2019
DOI: 10.1093/toxsci/kfz175
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Gamma-Glutamyltransferase Activity and Consequent Pro-oxidant Reactions in Human Macrophages Exposed to Crocidolite Asbestos

Abstract: Asbestos is the main causative agent of malignant pleural mesothelioma. The variety known as crocidolite (blue asbestos) owns the highest pathogenic potential, due to the dimensions of its fibers as well as to its content of iron. The latter can in fact react with macrophage-derived hydrogen peroxide in the so called Fenton reaction, giving rise to highly reactive and mutagenic hydroxyl radical. On the other hand, hydroxyl radical can as well originate after thiol-dependent reduction of iron, a process capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It is well known that asbestos fibers can induce alterations in the immune system, while being involved in the inflammatory process 40 42 . Different studies have reported miR-197-3p as being significantly down-regulated in inflammatory conditions 43 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that asbestos fibers can induce alterations in the immune system, while being involved in the inflammatory process 40 42 . Different studies have reported miR-197-3p as being significantly down-regulated in inflammatory conditions 43 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that asbestos fibers can induce alterations in the immune system, while being involved in the inflammatory process [40][41][42] . Different studies have reported miR-197-3p as being significantly down-regulated in inflammatory conditions 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to H 2 O 2 generated from NOX, another source of ROS in macrophages is identified as γ-glutamyltransferase (GGT), which is found in exposure to crocidolite and neuroinflammation. The oxidative injury and clinical signs in neuroinflammation can be suppressed by targeting GGT activity [ 86 , 87 ]. Compared with M1 macrophages, M2 macrophages have lower levels of ROS and hydrogen peroxide, which implies M1 types’ pro-inflammatory and M2 types’ anti-inflammatory functions [ 88 ] (Fig.…”
Section: Background Of Macrophagementioning
confidence: 99%